Is math anxiety caused by a deficit in basic numerical skills? A study using numerical and non-numerical tasks - García-Orza, Javier; Carratalá Cepedal, Patricia (My University, 2013)
Recent research found differences between high and low anxiety adults in basic numerical tasks like Arabic number comparison and dot enumeration (Maloney et al., 2010; 2011). This led some researchers to consider that math anxiety could be motivated by a subtle deficit in processing quantities. However, most of these studies did not controlled for some relevant variables, hence the difficulties found in basic tasks could be motivated by differences in working memory or in “general” anxiety between the high and low math anxiety groups. In the present research working memory skills and trait and mood anxiety were assessed in 15 low anxiety and 15 high anxiety 6th grade students, then both groups took part in three experiments. In the first, dot comparison task, bigger effects of distance and magnitude were found in the high anxiety group. In Experiment 2, Arabic number comparison, however, the only difference between both groups was related to speed: low anxiety participants were faster. Similar differences were found in Experiment 3, in which participants were required to perform an attentional (Posner) task without numerical content. It is concluded that the relationship between performance and math anxiety is more complex than previously thought.
Keywords: Números - Proceso de datos; Number processing; Working memory; Math anxiety